2021
DOI: 10.1002/alr.22794
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of measures of disease severity in rhinitis

Abstract: Background: Rhinologists often encounter a broad spectrum of allergic rhinitis (AR) and nonallergic rhinitis (NAR) patients, who can be variably classified based upon timing and severity of disease. Our understanding of the varied quality of life (QOL) impact in different classifications of rhinitis is limited. Thus a more comprehensive understanding of the impact of rhinitis upon our patients, as measured by both patient reported outcome measures (PROMs) and clinical physiologic measures, as well as unique fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The mTNSS of 4.32 in our study population was lower than that reported in the existing literature and summarized in a recent review (pooled mean TNSS = 6.06). 32 We attributed this discrepancy to the differences in study settings, wherein studies assessing TNSS were frequently against a clinical backdrop, resulting in study samples comprising patients perceiving their AR as sufficiently severe so as to warrant treatment and meriting a higher TNSS. 33 Indeed, one study which occurred in a non-clinical setting similar to ours reported lower mean TNSS in rhinitics.…”
Section: Discussionmentioning
confidence: 99%
“…The mTNSS of 4.32 in our study population was lower than that reported in the existing literature and summarized in a recent review (pooled mean TNSS = 6.06). 32 We attributed this discrepancy to the differences in study settings, wherein studies assessing TNSS were frequently against a clinical backdrop, resulting in study samples comprising patients perceiving their AR as sufficiently severe so as to warrant treatment and meriting a higher TNSS. 33 Indeed, one study which occurred in a non-clinical setting similar to ours reported lower mean TNSS in rhinitics.…”
Section: Discussionmentioning
confidence: 99%
“…The TOSS was less well correlated with RQLQ and VAS-RS. 5 Although ocular symptoms are bothersome and affect RQLQ, RQLQ may not be optimal at reflecting ocular symptoms. Furthermore, the TOSS scale displays some limitations, as it only assesses two items (eye itching and tearing), displaying a lower contribution to TSS.…”
Section: Patient-reported Outcome Measures In Birch Pollen Allergic P...mentioning
confidence: 99%
“…High quality evidence evaluating the impact of AR on QOL continues to show AR patients suffer from decreased general and disease‐specific QOL due to impacts on physical and mental health 1042–1047 . These studies also show that treatment of AR with INCS, oral antihistamines, and AIT leads to improved QOL.…”
Section: Allergic Rhinitis Disease Burdenmentioning
confidence: 97%